2016
DOI: 10.1177/107327481602300207
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vismodegib in the Management of Advanced Periocular Basal Cell Carcinoma

Abstract: Too few cases exist to draw any conclusions on the role that vismodegib might play in the management of periocular BCC. In addition, long-term follow-up data are not yet available. Although the objective response rate of advanced BCC is impressive in study patients receiving vismodegib, well-controlled clinical studies are needed to determine whether vismodegib has any impact on survival or quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…For basal cell carcinomas, the hedgehog pathway inhibitor vismodegib has shown good results for locally advanced tumors (26). Some authors have shown that vismodegib can prevent the need for orbital exenteration for periocular tumors (27), with complete response rates up to 67% (28,29), but this evidence is limited by the small number of cases. Targeted immunotherapy also appears to play a role in locally advanced skin cancers, but more robust supporting evidence is still needed (30).…”
Section: ' Discussionmentioning
confidence: 99%
“…For basal cell carcinomas, the hedgehog pathway inhibitor vismodegib has shown good results for locally advanced tumors (26). Some authors have shown that vismodegib can prevent the need for orbital exenteration for periocular tumors (27), with complete response rates up to 67% (28,29), but this evidence is limited by the small number of cases. Targeted immunotherapy also appears to play a role in locally advanced skin cancers, but more robust supporting evidence is still needed (30).…”
Section: ' Discussionmentioning
confidence: 99%
“…Another review conducted for the periocular treatment with Vismodegib reports a complete regression of 30% of patients, with follow-up less than 5 months. However, further randomized-controlled-trials are needed to investigate whether the use of Vismodegib in periocular BCC has an impact on local tumor control, survival, or quality of life (21). Figures 1,2 show periocular BCC before and after treatment with Vismodegib (22).…”
Section: Hedgehog-inhibitorsmentioning
confidence: 99%
“…The authors documented a significant complete clinical response in 141 of 384 patients (37%) after a mean duration of vismodegib treatment of 36.7 weeks (range: 11-100 weeks) for nonmetastatic patients. 4,[7][8][9][10][11][12][13][14]18,[24][25][26][27] Information concerning the treatment choice was available for 325 patients (84.6%, 325/384) and complete remission was found to be achieved exclusively by medical treatment for 110 patients (33.8%, 110/325), for 20 patients (6.1%, 20/325) by vismodegib followed by surgery, and for 3 patients (0.9%, 3/325) by vismodegib followed by surgery and radiotherapy. For 58 patients treated by an association of vismodegib and radiotherapy, it was not possible to find the overall treatment response.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…In advanced BCC, the Hedgehog signaling pathway inhibitor vismodegib is becoming key treatment and has recently been enhanced by combination with PD-1 inhibitor therapy. [3][4][5] When vismodegib is used as neoadjuvant therapy, the ERIVANCE BCC study showed that it had a response rate of 30% for metastatic BCC and 43% for locally advanced BCC, 3 and for periocular locally advanced BCC, the STEVIE trial study reported complete response rate of 28.9%. The outcomes of patients treated by vismodegib as neoadjuvant therapy are now well documented in response rate or adverse events, but to date, few studies have provided an overview of the functional issues regarding eyelid sclerosis after treatment and the need of complementary resection or local reconstruction.…”
mentioning
confidence: 99%